To Be or Not to Be... An Antioxidant? That Is the Question - José M. Palma; Isabel Seiquer (MDPI AG, 2020)
The concept of antioxidants refers to a substance with the capacity to either directly scavenge or indirectly prevent the formation of pro-oxidant molecules, basically associated to the so called reactive oxygen species (ROS) [...]